Model Pendidikan Islam Berbasis Keluarga yang Adaptif di Era Digital dan Kecerdasan Buatan: Telaah Literatur, Teks, dan Konteks - Hasanah, Risqiatul; Maseri, Ani Cahyadi (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
The era of digital disruption, marked by the rapid advancement of Artificial Intelligence (AI), has significantly impacted various aspects of life, including the Islamic education system. In this context, the family as the first and foremost educational institution is confronted with both new challenges and opportunities in instilling Islamic values in the younger generation. This article aims to examine the urgency of developing a family-based Islamic education model that is adaptive to the advancement of digital technology and AI. This study employs a literature review method with a multidisciplinary approach, which includes: (1) an exploration of classical and contemporary literature on the concept of family education in Islam; (2) a normative analysis of the primary sources of Islamic teachings, namely the Qur’an and Hadith, concerning the role and responsibilities of the family in education; and (3) a contextual analysis of the dynamics, challenges, and opportunities facing Muslim family education in the modern 21st century. The findings of this study indicate that effective family education in the digital age requires the integration of foundational Islamic values with parenting and educational strategies that are responsive to technological developments. Moreover, it necessitates a family education model that is not only normatively grounded but also adaptive to the changing times, collaborative between families and their environments, and contextualized to the social realities of today’s Muslim communities.